Analisis Pengaruh Pendidikan, Upah Pekerja dan Akses Sanitasi Layak Terhadap Pendapatan Per Kapita di Indonesia Tahun 2023 - Rifdianti, Shinta; Irianto, Hikmal Mardian; Hariaddin, Muhammad; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2025)
Economic welfare disparity across regions in Indonesia remains a challenge in achieving the Sustainable Development Goals (SDGs), particularly Goal 8: decent work and economic growth. One of the key indicators reflecting economic well-being is per capita income. This study aims to analyze the influence of socio-economic variables namely the percentage of high school graduates, average worker wages, and access to proper sanitation on per capita income across 34 Indonesian provinces in 2023. Data were obtained from official publications of Statistics Indonesia (BPS) and analyzed using multiple linear regression to examine the significance of the relationships between variables. The results indicate that all three independent variables have a positive and significant effect on per capita income. These findings highlight the importance of improving secondary education quality, wage protection, and equitable access to sanitation services in promoting inclusive and welfare-based economic growth.